2001
DOI: 10.1051/0004-6361:20010707
|View full text |Cite
|
Sign up to set email alerts
|

Stability of the extragalactic VLBI reference frame

Abstract: Abstract. The qualification and the maintenance of the International Celestial Reference Frame (ICRF) source directions are currently based on global statistics regarding the complete data set of VLBI observations of extragalactic radio sources. The founding hypothesis in the selection of extragalactic objects to access a quasi-inertial reference system is that their directions are fixed in space. Therefore the study of the time variability of the sources is an important step in the process of checking and imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 8 publications
1
30
0
Order By: Relevance
“…4 and 5 in the form of wavelet analysis . Figure 4, which considers all sources (Conventional approach), shows energy in the 1984-1990 time frame that disappears after 1990, in agreement with the Gontier et al (2001) stability diagnosis mentioned in Sect. 5.…”
Section: Prograde Ficnsupporting
confidence: 82%
See 1 more Smart Citation
“…4 and 5 in the form of wavelet analysis . Figure 4, which considers all sources (Conventional approach), shows energy in the 1984-1990 time frame that disappears after 1990, in agreement with the Gontier et al (2001) stability diagnosis mentioned in Sect. 5.…”
Section: Prograde Ficnsupporting
confidence: 82%
“…Note that perturbation induced by the 163 unstable sources alone is not particularly large. Gontier et al (2001) have shown that the general improvements in VLBI technology and observing strategies brought the astrometric results to their current precision towards the end of the 1980's. Starting about 1990, individual source coordinates stabilised.…”
Section: Precession and Obliquity Ratementioning
confidence: 99%
“…The artificial displacement of the sources towards the poles was already noticed in several earlier works (e.g., Ma et al 1998;Gontier et al 2001;Feissel-Vernier 2003). It can be physically understood as resulting from the dissymmetry of the network: during the first two decades of VLBI, most of the antennas (and most of the observed sources) were in the northern hemisphere.…”
Section: Systematicsmentioning
confidence: 57%
“…The referencing of the session results to ITRF2000 includes a no-net-translation condition, the use of the corresponding EOP, and no adjustment in scale (Ma, personal communication). Results were used starting in 1990, when the operation of the VLBI network reached a first maturity stage (Gontier et al, 2001). …”
Section: Data Pedigreementioning
confidence: 99%